2021
DOI: 10.3390/jcm10112347
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hypermethylation of FcγR2B in Leukocytes of Patients with Kawasaki Disease

Abstract: The Fc gamma receptor family contains several activating receptors and the only inhibitory receptor, FcγR2B. In this study, we investigated the dynamic methylation change of FcγR2B in different stages of Kawasaki disease (KD). We enrolled a total of 116 participants, which included patients with febrile diseases as controls and KD patients. Whole blood cells of KD patients were collected prior to intravenous immunoglobulin (IVIG) treatment (KD1), three to seven days after IVIG (KD2), three weeks after IVIG tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…CRP, neutrophils, and albumin have been commonly used parameters for measuring the activity of inflammatory conditions. [7] Previous reports have indicated that low serum albumin levels due to vasculitis and plasma leakage were correlated with nutrition and immune status and associated with IVIG treatment failure in KD patients, intensive care unit admission, and coronary artery lesions. Vascular leakage was suspected to not only result in hypoalbuminemia but also to allow allergens from the respiratory tract into the sub-epithelial space and circulation and further sensitization.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…CRP, neutrophils, and albumin have been commonly used parameters for measuring the activity of inflammatory conditions. [7] Previous reports have indicated that low serum albumin levels due to vasculitis and plasma leakage were correlated with nutrition and immune status and associated with IVIG treatment failure in KD patients, intensive care unit admission, and coronary artery lesions. Vascular leakage was suspected to not only result in hypoalbuminemia but also to allow allergens from the respiratory tract into the sub-epithelial space and circulation and further sensitization.…”
Section: Discussionmentioning
confidence: 97%
“…As a result, IVIG is also suspected to be one of the reasons for the increase in allergic diseases after KD [6]. The anti-inflammatory mechanisms of IVIG include saturating Fc receptors and inhibitory effects on the mRNA expression of Fc receptors, lowering the production of cytokines, and on epigenetic modulation to increase gene methylation [7,8]. Among patients treated with IVIG, only patients with hyper immunoglobulin(Ig) E syndrome or atopic dermatitis had decreased IgE levels after treatment, and levels in patients with KD or idiopathic thrombocytopenic purpura were unchanged [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, considerable evidence has shown ongoing inflammation in the coronary artery of KD. Serological evidence of ongoing systemic inflammation has been noted in those patients with persistent aneurysms, with higher levels of serum amyloid A and interleukin-6, high sensitivity C-reactive protein, hypermethylation of FcγR2B in leukocytes, and imaging evidence by PET scanning ( 7 ). Additional anti-inflammation treatment may be needed for KD patients with aneurysm formation.…”
Section: Introductionmentioning
confidence: 99%